YTTRIUM OXYFLUORIDE SINTERED BODY AND METHOD FOR MANUFACTURING BODY OF YTTRIUM OXYFLUORIDE SINTERED BODY
By using high fluoride content yttrium fluoride powder as a bonding agent in the semiconductor manufacturing process, the problems of equipment corrosion and particle deposition are solved, and the stable connection and strength of complex-shaped yttrium fluoride forged bodies are achieved, and the product quality is improved.
Patent Information
- Application Number
- JP2021112856
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-07
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2041-07-07
AI Technical Summary
During semiconductor manufacturing, the use of corrosive gases and plasmas leads to equipment corrosion and particle deposition, resulting in product defects, and existing ceramic materials are difficult to deal with forged bodies of complex shapes.
The yttrium oxyfluoride powder with a higher fluoride content is used as the bonding agent to reduce the softening point of the bonding agent by increasing the fluoride content in the bonding agent, thereby maintaining the strength and flexibility of the bonding during the forging process.
The stable connection and strength of the use of complex shapes of yttrium oxyfluoride forged bodies in semiconductor manufacturing is achieved, avoiding equipment corrosion and particle deposition, and improving product quality and reliability.
Smart Images

Figure 0007659459000002 
Figure 0007659459000003 
Figure 0007659459000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a joined body of yttrium oxyfluoride sintered bodies and a method for producing a joined body of yttrium oxyfluoride sintered bodies.
[0002] Fluorine-based corrosive gases and chlorine-based corrosive gases and plasmas using these gases are used in various steps in the manufacture of semiconductors, particularly in the steps of dry etching, plasma etching and cleaning.
[0003] When these corrosive gases and plasmas are used, the components of the semiconductor manufacturing equipment can corrode, and fine particles that peel off from the surfaces of the components can adhere to the surface of the semiconductor, easily causing product defects. For this reason, ceramics that are highly resistant to corrosion by halogen-based plasmas must be used as bulk materials for the components of the semiconductor manufacturing equipment.
[0004] As such bulk materials, aluminum oxide, yttrium oxide, aluminum-yttrium composite oxide, and yttrium fluoride have been proposed (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2011-136877 A [Patent Document 2] JP 2013-144622 A Summary of the Invention [Problem to be solved by the invention]
[0006] In the manufacture of semiconductors, sintered bodies, which are bulk materials, are made of the same material on the surface and inside, and there is little risk of impurity contamination even if they are worn out. However, in the manufacture of semiconductors, various shapes of semiconductor manufacturing equipment parts are used, and sintered bodies, which are difficult to process, are difficult to process into complex shapes.
[0007] In view of the above problems, the present invention aims to provide a joint of yttrium oxyfluoride sintered bodies and a method for manufacturing a joint of yttrium oxyfluoride sintered bodies so that a yttrium oxyfluoride sintered body can be provided even if it has a complex shape. [Means for solving the problem]
[0008] The joined body of yttrium oxyfluoride sintered bodies of the present invention is a joined body of yttrium oxyfluoride sintered bodies comprising a first region and a second region facing the first region across an interface region, and the interface region has a higher porosity than the first region and the second region.
[0009] Since the yttrium oxyfluoride sintered body contains fluorine, it is likely to soften and deform when heated during sintering or use. In the bonded body of the yttrium oxyfluoride sintered body of the present invention, the interface region, which is the bonded portion, has a higher porosity than the first and second regions, which are the sintered bodies, so that even if the first and second regions are deformed during the sintering process, etc., and the clearance changes, the pores act as a cushion to absorb the change and maintain the bond. Therefore, a bonded body of the yttrium oxyfluoride sintered body that can easily accommodate even complex shapes can be obtained.
[0010] In the joined body of yttrium oxyfluoride sintered bodies of the present invention, the interface region preferably has a porosity of 2 to 60%. When the porosity in the interface region is 2% or more, the density can be sufficiently reduced to allow the thermal stress to be dispersed appropriately, and when the porosity in the interface region is 60% or less, sufficient bonding strength can be secured to prevent peeling. The porosity in each region can be obtained from the cross-sectional area ratio of the pores in the cross section of the bonded yttrium oxyfluoride sintered body, and can be actually obtained by calculating the ratio of the pores in a scanning electron microscope photograph taken at a magnification of 500 to 10,000. It can be determined by element mapping whether the pores are a resin filled in the pores for fixing or a component of the sintered body. Furthermore, when the thickness of the interface region is not sufficiently thicker than the average diameter of the constituent structure (10 times or less), the porosity of the interface region can also be obtained by calculating the ratio of the length of the portion where particles such as yttrium fluoride that constitute the interface region are present to the length of the pore portion on the center line that is equidistant from the boundary line between the interface region and the first region or the second region in the above scanning electron microscope photograph.
[0011] In the joined yttrium oxyfluoride sintered body of the present invention, it is desirable that YF3 and Y5O4F7 are the main components, and that the interface region has a higher YF3 content than the first region and the second region.
[0012] In a bonded body, the interface region is a weak portion because it is originally made of separate materials. By increasing the content of fluorine, which has the effect of lowering the melting point, in this weak interface region, the following advantages are obtained. In the yttrium oxyfluoride sintered body, fluorine is not a heterogeneous element, so even if the content of fluorine increases, it does not become an impurity. In addition, since fluorine is easy to diffuse, fluorine diffuses in the yttrium oxyfluoride sintered body near the interface region, and the part with a low softening point diffuses, making the concentration gradient of fluorine gentle and making it difficult to generate stress concentration. Therefore, it is possible to obtain a joint of yttrium oxyfluoride sintered bodies with strength.
[0013] In the joined yttrium oxyfluoride sintered body of the present invention, the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the interface region is desirably 101 to 150% of the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the first region and the second region.
[0014] When the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the interface region is 101% or more of the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the first and second regions, the bonding strength between the interface region and the first and second regions can be sufficiently ensured. Furthermore, when the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the interface region is 150% or less of the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the first and second regions, the formation of YF3, which has a larger thermal expansion than Y5O4F7, is suppressed, the difference in thermal expansion between the interface region and the first and second regions can be reduced, and thermal shock resistance can be ensured.
[0015] The ratio of the content of YF3 to the total content of Y5O4F7 and YF3 in the interface region can be obtained from the cross-sectional area ratio of YF3 and Y5O4F7 in the cross section of the joint of the yttrium oxyfluoride sintered body, and can actually be obtained by calculating the ratio from a scanning electron microscope photograph taken at a magnification of 500 to 10,000. In addition, since the ratio calculated from the cross-sectional area is directly used as the content ratio, the content ratio is a volume ratio. Furthermore, when the thickness of the interface region is not sufficiently thicker than the average diameter of the constituent structures (10 times or less), the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the interface region can also be obtained by calculating the ratio of the length of the YF3 structure portion constituting the interface region to the length of the Y5O4F7 structure at a center line equidistant from the boundary line between the interface region and the first region or the second region in the above scanning electron microscope photograph.
[0016] The texture of the interface region is preferably finer than the texture of the first and second regions. Note that a texture is a region that is composed of the same composition, and in this embodiment, there are YF3 textures and Y5O4F7 textures.
[0017] If the structure of the interface region is finer than the structures of the first and second regions, even if stress concentration or the like occurs and a large force is applied to the interface region, the finer structure of the interface region makes it stronger and less likely to break.
[0018] The method for producing a joined body of yttrium oxyfluoride sintered bodies of the present invention includes a joining step of sintering a joining surface of a first yttrium oxyfluoride sintered body and a joining surface of a second yttrium oxyfluoride sintered body by sandwiching yttrium oxyfluoride powder having a higher fluorine content than the first and second yttrium oxyfluoride sintered bodies.
[0019] Fluorine has the effect of lowering the melting point of yttrium oxyfluoride and acts as a sintering aid, so that by sandwiching yttrium oxyfluoride powder with a high fluorine content between the joining surfaces and sintering them, the first and second yttrium oxyfluoride sintered bodies can be joined without deforming or damaging them. In addition, the yttrium oxyfluoride with a high fluorine content may be yttrium oxyfluoride powder having a high YF content in the particles themselves, or the fluorine content may be increased by adjusting the ratio of a mixture of yttrium oxyfluoride and yttrium fluoride. In addition, the "yttrium oxyfluoride" in the yttrium oxyfluoride powder includes not only complete Y5O4F7 but also the YF3 phase.
[0020] In the method for producing a joined body of yttrium oxyfluoride sintered bodies of the present invention, the joining step is preferably carried out at 700 to 1200°C.
[0021] By carrying out the bonding process at 700° C. or higher, the excess fluorine acts as a sintering aid to form a strong bond, while by carrying out the bonding process at 1200° C. or lower, the sintering of the first and second yttrium oxyfluoride sintered bodies is prevented from progressing, and deformation and shrinkage can be prevented.
[0022] In the method for producing a joined body of yttrium oxyfluoride sintered bodies of the present invention, it is preferable that a slurry containing the yttrium oxyfluoride powder and a solvent is applied in the joining step.
[0023] By dissolving yttrium oxyfluoride powder in a solvent to form a slurry, the fluidity is improved, and the interface region can be made thinner. The interface region is inferior in strength to the bonded body (first region) of the first yttrium oxyfluoride sintered body or the bonded body (second region) of the second yttrium oxyfluoride sintered body, but by making the interface region thinner, interpenetration of atoms between the first and second yttrium oxyfluoride sintered bodies progresses during the sintering process, and the decrease in strength can be suppressed.
[0024] In the method for producing a joined body of yttrium oxyfluoride sintered bodies of the present invention, the solvent is preferably ethanol or methanol.
[0025] Ethanol and methanol have a low boiling point and a small surface energy, so they easily penetrate into the pores. Therefore, only the solvent from the slurry sandwiched between the first and second yttrium oxyfluoride sintered bodies easily penetrates into the sintered body, making it easier to form a thin interface region. Effect of the Invention
[0026] It is possible to provide a joined body of yttrium oxyfluoride sintered bodies and a method for manufacturing a joined body of yttrium oxyfluoride sintered bodies so that yttrium oxyfluoride can be provided even if it has a complex shape. [Brief description of the drawings]
[0027] [Figure 1] 1 is a flowchart showing a first embodiment of a method for producing a joined body of yttrium oxyfluoride sintered bodies according to the present invention. [Diagram 2] 5 is a flowchart showing a second embodiment of a method for producing a joined body of yttrium oxyfluoride sintered bodies according to the present invention. [Diagram 3]1 is a scanning electron microscope photograph of a cross section of a joined body of yttrium oxyfluoride sintered bodies obtained in Example 1. [Figure 4] 2 is an enlarged photograph of a first yttrium oxyfluoride sintered body (first region) in a scanning electron microscope photograph of a cross section of a joined body of yttrium oxyfluoride sintered bodies obtained in Example 1. [Diagram 5] 2 is an enlarged photograph of an interface region in a scanning electron microscope photograph of a cross section of a joined body of yttrium oxyfluoride sintered bodies obtained in Example 1. [Figure 6] 1 is a scanning electron microscope photograph of a cross section of a joined body of yttrium oxyfluoride sintered bodies obtained in Example 2. [Figure 7] 1 is a scanning electron microscope photograph of a cross section of a joined body of yttrium oxyfluoride sintered bodies obtained in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] <Yttrium oxyfluoride sintered body> The joined body of yttrium oxyfluoride sintered bodies of the present invention is a joined body of yttrium oxyfluoride sintered bodies comprising a first region and a second region facing the first region across an interface region, and the interface region has a higher porosity than the first region and the second region.
[0029] In the bonded body of the yttrium oxyfluoride sintered body of the present invention, the interface region, which is the bonded portion, has a higher porosity than the first and second regions, which are the sintered bodies, so that even if the first and second regions are deformed during the sintering process, etc., and a change in clearance occurs, the pores act as a cushion to absorb the change and maintain the bond. Therefore, it is possible to obtain a yttrium oxyfluoride sintered body that can easily accommodate even complex shapes.
[0030] The first and second regions are mainly composed of Y5O4F7 and YF3. The term "main component" means that the component accounts for 90 mol % or more of the total components.
[0031] The first region and the second region preferably have a porosity of 0.1 to 1%. If the porosity in the first region and the second region is within the above range, sufficient strength can be imparted to the first region and the second region.
[0032] The interface region preferably has a porosity of 2 to 60%. When the porosity in the interface region is 2% or more, the density can be sufficiently reduced to allow the thermal stress to be dispersed appropriately, and when the porosity in the interface region is 60% or less, sufficient bonding strength can be secured to prevent peeling.
[0033] The interface region desirably has a higher YF3 content than the first region and the second region.
[0034] In a bonded body, the interface region is a weak portion because it is originally made of separate materials. By increasing the content of fluorine, which has the effect of lowering the melting point, in this weak interface region, the following advantages are obtained. In the yttrium oxyfluoride sintered body, fluorine is not a heterogeneous element, so even if the content of fluorine increases, it does not become an impurity.In addition, since fluorine is easy to diffuse, fluorine diffuses in the yttrium oxyfluoride sintered body near the interface region, and the part with a low softening point diffuses, making the concentration gradient of fluorine gentle and making it difficult to generate stress concentration.Therefore, it is possible to obtain a joint of yttrium oxyfluoride sintered bodies with strength.
[0035] In the joined yttrium oxyfluoride sintered body of the present invention, the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the interface region is desirably 101 to 150% of the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the first region and the second region.
[0036] When the ratio of the content of YF3 to the total content of Y5O4F7 and YF3 in the interface region is 101% or more of the ratio of YF3 to the total content of Y5O4F7 and YF3 in the first and second regions, sufficient bonding strength of the interface can be ensured. Note that the ratio of the content of YF3 to the total content of Y5O4F7 and YF3 is a volume ratio. Furthermore, when the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the interface region is 150% or less of the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the first and second regions, the formation of yttrium fluoride, which has a larger thermal expansion than yttrium oxyfluoride, is suppressed, the difference in thermal expansion between the interface region and the first and second regions is reduced, and thermal shock resistance is ensured.
[0037] The texture of the interface region is preferably finer than the textures of the first region and the second region. For example, the texture of the interface region is preferably 0.1 to 10 μm in size. On the other hand, the texture of the first region and the second region is preferably 0.2 to 20 μm in size. The size of the structure can be measured by comparing the size of the constituent structures with a standard scale using a scanning electron microscope. Since YF3 and Y5O4F7 are observed with different concentrations using a scanning electron microscope, elemental mapping is performed in advance to identify the components.
[0038] If the structure of the interface region is finer than the structures of the first and second regions, even if stress concentration or the like occurs and a large force is applied to the interface region, the fine structure of the interface region makes it less likely to be destroyed.
[0039] The shapes and sizes of the first and second regions are not particularly limited, and can be appropriately set depending on the desired processing.
[0040] The thickness of the interface region is preferably 0.1 to 200 μm, and more preferably 1 to 10 μm. The thickness of the interface region can be measured by observing a cross section of the joined yttrium oxyfluoride sintered body using a scanning electron microscope.
[0041] <Method for producing a joined body of yttrium oxyfluoride sintered bodies> The method for producing a joined body of yttrium oxyfluoride sintered bodies of the present invention includes a joining step of sintering a joining surface of a first yttrium oxyfluoride sintered body and a joining surface of a second yttrium oxyfluoride sintered body by sandwiching yttrium oxyfluoride powder having a higher fluorine content than the first and second yttrium oxyfluoride sintered bodies.
[0042] Fluorine has the effect of lowering the melting point of yttrium oxyfluoride and acts as a sintering aid, so that by sandwiching yttrium oxyfluoride powder with a high fluorine content between the joining surfaces and sintering them, the first and second yttrium oxyfluoride sintered bodies can be joined without deforming or damaging them.
[0043] A method for producing a joined body of yttrium oxyfluoride sintered bodies according to the present invention will be described based on a first embodiment and a second embodiment.
[0044] [First embodiment] The joined body of yttrium oxyfluoride sintered bodies of the first embodiment is obtained according to the flow chart shown in FIG. FIG. 1 is a flow chart showing a first embodiment of a method for producing a joined body of yttrium oxyfluoride sintered bodies according to the present invention. As shown in FIG. 1, the first embodiment includes bonding surface preparation, raw material preparation, slurrying, interface region formation, compression bonding, drying, and sintering.
[0045] (Joint surface adjustment) In the first embodiment, first, the bonding surfaces of the yttrium oxyfluoride sintered bodies (first and second yttrium oxyfluoride sintered bodies) to be bonded to each other are adjusted. It may be a flat surface, or a curved surface having the same curvature, etc., as long as the gap is uniform when they are opposed to each other, there is no particular limitation. The joining surfaces may be adjusted by any method such as machining, polishing, or co-sintering.
[0046] (raw material adjustment) Next, the yttrium oxyfluoride powder used for bonding is adjusted. The adjustments include the component ratio, average particle size, and, if the powder is in granular form, may be crushed.
[0047] The yttrium oxyfluoride powder is adjusted, for example, by the ratio of Y5O4F7 to YF3 so that it softens at a lower temperature than the sintered body, and the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the yttrium oxyfluoride powder is adjusted to be greater than the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the first and second yttrium oxyfluoride sintered bodies. For example, the ratio of the content of YF3 to the total content of Y5O4F7 and YF3 of the yttrium oxyfluoride powder is preferably 101 to 150% of the ratio of the content of YF3 to the total content of Y5O4F7 and YF3 of the first and second yttrium oxyfluoride sintered bodies. The component ratio may be adjusted by using a yttrium oxyfluoride powder with a high ratio of YF3, or by adding YF3. By containing a large amount of fluorine, the joining portion (interface region) softens faster than the sintered bodies to be joined, and joining can be performed without deforming the overall shape.
[0048] Although the average particle size of the yttrium oxyfluoride powder is not particularly limited, it is preferable to use a powder that is finer than the structure that constitutes the yttrium oxyfluoride sintered body. For example, the average particle size is preferably 0.1 to 10 μm. Furthermore, when the yttrium oxyfluoride powder is bound with a binder to form granules, it may be fired to remove the binder, or crushed to break down into individual particles. The average particle size of the yttrium oxyfluoride powder can be determined by a laser diffraction particle size distribution measuring device. Specifically, in the cumulative volume distribution curve of particles obtained by the above-mentioned measuring device, the particle diameter at which the cumulative volume is 50% by volume from the smallest particle diameter is the average particle diameter.
[0049] (Slurrying) In the joining step, it is preferable to apply a slurry containing yttrium oxyfluoride powder and a solvent. The yttrium oxyfluoride powder obtained in the raw material preparation is slurried so that it can be spread thinly. This improves fluidity and allows the interface region to be made thinner. The interface region itself is inferior in strength to the first yttrium oxyfluoride sintered body or the second yttrium oxyfluoride sintered body, but by making the interface region thin, interpenetration of atoms between the first and second yttrium oxyfluoride sintered bodies proceeds during the sintering process, and the decrease in strength can be suppressed.
[0050] Examples of the solvent include water, alcohol, acetone, ether, and other volatile solvents. Among these, ethanol or methanol is preferable. Ethanol and methanol have a low boiling point and a small surface energy, so they easily penetrate into the pores. Therefore, only the solvent from the slurry sandwiched between the first and second yttrium oxyfluoride sintered bodies easily penetrates into the sintered body, making it easier to form a thin interface region.
[0051] The concentration of the slurry is not particularly limited, but it is preferable that the powder is 60 to 90% by weight based on the total weight of the slurry. If the powder content is 60% by weight or more, a sufficient thickness can be secured to act as a cushion even if the joining surface is deformed. If the powder content is 90% by weight or less, no excess powder remains and a thin interface region is formed. A thin interface region can improve dimensional accuracy, and also reduce the volume ratio of the interface region, which is prone to having low strength, making it less susceptible to breakage.
[0052] (interfacial region formation) Next, the slurry obtained by the slurrying is applied to the joining surfaces. The method of application is not particularly limited, but the slurry may be applied to the center of the joining surfaces so that the slurry spreads over the entire interface, and then gradually spread from the center. This allows the interface region to be formed.
[0053] (Crimping) The applied slurry is pressed so that no air bubbles remain in the entire interface area. Gradually apply pressure to spread the slurry applied to the center of the joining surface over the entire area in order to prevent air bubbles from remaining. The slurry applied to the center does not contain air bubbles, so by spreading it over the entire area, it can be spread over the entire interface area without air bubbles being trapped inside the slurry. The pressure bonding may be performed by simply applying pressure, but the sintered body may also be rocked or rotated to spread the slurry evenly.
[0054] (Dry) After the slurry has spread over the bonding surface (interface region), the solvent is dried. The solvent may be dried by diffusing little by little from the gaps in the bonding surface, but by using a solvent that has good wettability with the yttrium oxyfluoride sintered body, the solvent can be diffused not only in the direction of the bonding surface but also in the direction perpendicular to the bonding surface by propagating through the open pores of the sintered body, so that both the side close to the outer surface and the center can be quickly dried. During drying, if bubbles are generated in the slurry at the center of the interface, the bonding strength will decrease, so it is desirable to maintain the temperature below the boiling point of the solvent for 0.1 hours or more to thoroughly remove the solvent. After that, the temperature can be raised further above the boiling point of the solvent to completely remove the solvent, or the temperature can be lowered once and the solvent can be completely removed in the next sintering stage. The desired drying temperature is not particularly limited, but when ethanol is used, for example, it is preferable to maintain the temperature below the boiling point at 0 to 50°C for 0.1 to 5 hours, and to maintain the temperature above the boiling point at 80 to 200°C for 0.1 to 5 hours.
[0055] (Sintering) The slurry is dried at the interface between the two sintered bodies, and then sintered. The sintering atmosphere is preferably an inert atmosphere, and the temperature is preferably 700 to 1200°C. If the sintering temperature is 700°C or higher, the sintering of the yttrium oxyfluoride powder supplied as the slurry can be promoted and bonded with sufficient strength. If the sintering temperature is 1200°C or lower, the softening of the two sintered bodies can be prevented, the deformation of the original sintered body can be prevented, and a bonded body of yttrium oxyfluoride sintered bodies with high dimensional accuracy can be obtained. Note that the yttrium oxyfluoride powder supplied as a slurry has a higher fluorine content than the yttrium oxyfluoride sintered body, so it is easy to soften at a low temperature and easy to sinter at a low temperature.
[0056] In the yttrium oxyfluoride sintered body obtained by the above process, the first yttrium oxyfluoride sintered body constitutes the first region, the second yttrium oxyfluoride sintered body constitutes the second region, and the yttrium oxyfluoride powder coated on the joining surface constitutes the interface region. The yttrium oxyfluoride powder used has a finer particle size than the structure of the sintered body, so the structure of the interface region is finer than the first and second regions. Also, by bonding at a lower temperature than the first and second regions so as not to advance sintering, the interface region is less likely to be densified and has a higher porosity than the first and second regions. The fluorine content of the yttrium oxyfluoride powder applied to the joining surface (fluorine content of the interface region) is higher than the fluorine content of the first yttrium oxyfluoride sintered body and the second yttrium oxyfluoride sintered body, so that although fluorine diffusion occurs gradually in the joining process, fluorine is unlikely to dissipate outside the joined yttrium oxyfluoride sintered body, and a joined body with a high fluorine content in the interface region is obtained. Note that, although there are cases in which the fluorine content of the interface region becomes equal to that of the first region and the second region by lengthening the sintering time or reducing the thickness of the slurry, even in this case, the interface region is less likely to crystallize than the first region and the second region, and the porosity is higher.
[0057] [Second embodiment] In a second embodiment of the present invention, the powder is sandwiched between sintered bodies and bonded together without forming a slurry. The joined body of yttrium oxyfluoride sintered bodies according to the second embodiment is obtained according to the flow chart shown in FIG. FIG. 2 is a flow chart showing a second embodiment of the method for producing a joined body of yttrium oxyfluoride sintered bodies of the present invention. As shown in FIG. 2, the second embodiment includes bonding surface preparation, raw material preparation, interface region formation, compression bonding, and sintering.
[0058] In the second embodiment, the steps up to the joining surface adjustment and raw material adjustment are performed in the same manner as in the first embodiment, and the yttrium oxyfluoride powder is joined without being slurried. This embodiment differs from the first embodiment in that there is no slurrying or drying. Accordingly, the steps after the formation of the interface region are partially different from the first embodiment, but can be performed in the same manner.
[0059] (interfacial region formation) As in the first embodiment, the obtained yttrium oxyfluoride powder is applied directly to the joining surfaces without being slurried. Since this is a dry method rather than a wet method, little flow can be expected during compression bonding, so the yttrium oxyfluoride powder is spread to a uniform thickness on the joining surfaces.
[0060] (Crimping) In the compression bonding, pressure is applied to the yttrium oxyfluoride powder sandwiched between the first yttrium oxyfluoride sintered body and the second yttrium oxyfluoride sintered body to increase density and facilitate subsequent sintering. Since this embodiment is a dry process, even if pressure is applied once, it is easy to separate, so sintering may be performed while clamped using a jig or tool. In addition, a load may be continuously applied using a weight so that pressure is continuously applied during sintering, and the process may proceed to sintering.
[0061] (Sintering) Sintering is carried out in the same manner as in the first embodiment.
[0062] In this embodiment, the coating (spraying) is performed in a dry manner, so that the yttrium oxyfluoride powder is unlikely to flow out from the bonding surface even when pressure is applied, and the amount of the powder sprayed directly becomes the thickness of the interface region (bonding layer). For this reason, it is important to apply the powder as thinly as possible with a uniform thickness.
[0063] In the bonded body obtained in this embodiment, the interface region has a higher porosity than the first region and the second region, as in the first embodiment, and the fluorine content in the interface region is higher than the fluorine content in the first region and the second region. In this embodiment, since the yttrium oxyfluoride powder has no fluidity, it is difficult to obtain a thin interface region, fluorine diffusion is difficult to occur, and the fluorine content in the interface region is likely to be high. EXAMPLES
[0064] The present invention will now be described in detail with reference to examples, but the present invention is not limited to these examples as long as they do not deviate from the gist of the present invention. In addition, unless otherwise specified, parts means parts by weight and % means % by weight.
[0065] Example 1 One sheet of yttrium oxyfluoride sintered body (approximately φ20 mm) was prepared and cut into a semicircular shape to obtain a first yttrium oxyfluoride sintered body and a second yttrium oxyfluoride sintered body. Granules having an average particle size of 20 μm, which were a uniform mixture of Y5O4F7 powder (70 parts by weight) having an average particle size of 4 μm and YF3 powder (30 parts by weight) having an average particle size of 3 μm, were uniformly dispersed on a first yttrium oxyfluoride sintered body, and then a second yttrium oxyfluoride sintered body was placed on top of the first yttrium oxyfluoride sintered body and sintered. The Y5O4F7 and YF3 powders do not contain any other components such as binders. Sintering was carried out by holding the mixture at 1000°C for 2 hours in an argon atmosphere.
[0066] The obtained first yttrium oxyfluoride sintered body and the second yttrium oxyfluoride sintered body were bonded to each other without being deformed, and became one plate (bonded body of yttrium oxyfluoride sintered bodies).
[0067] FIG. 3 is a scanning electron microscope photograph of a cross section of the joined body of yttrium oxyfluoride sintered bodies obtained in Example 1. In the bonded body 10 of yttrium oxyfluoride sintered bodies shown in Fig. 3, the dark layered part with scattered island-like parts in the center is the interface region 1, the light-colored part on the upper side of the interface region is the first yttrium oxyfluoride sintered body 2 (first region), and the light-colored part on the lower side of the interface region is the second yttrium oxyfluoride sintered body 3 (second region). In addition, many voids in the interface region 1 are pores 4, which are impregnated with a fixing resin. In the interface region 1 sandwiched between the first yttrium oxyfluoride sintered body 2 (first region) and the second yttrium oxyfluoride sintered body 3 (second region), the boundary was clear even after sintering.
[0068] FIG. 4 is an enlarged photograph of the first yttrium oxyfluoride sintered body (first region) in a scanning electron microscope photograph of a cross section of the joined yttrium oxyfluoride sintered body obtained in Example 1, and FIG. 5 is an enlarged photograph of the interface region in a scanning electron microscope photograph of the cross section of the joined yttrium oxyfluoride sintered body obtained in Example 1. In the enlarged photograph of the first yttrium oxyfluoride sintered body 2 shown in FIG. 4, the light-colored parts represent the Y5O4F7 structure 5, the dark-colored parts represent the YF3 structure 6, and the unevenly distributed voids represent the pores 4. Similarly, in the enlarged photograph of the interface region 1 shown in FIG. 5, the light-colored parts represent the Y5O4F7 structure 5, the dark-colored parts represent the YF3 structure 6, and the unevenly distributed voids represent the pores 4. As shown in FIGS. 4 and 5, in the interface region 1, a large number of small YF3 structures 6 are unevenly distributed, so that each of the Y5O4F7 structures 5 and YF3 structures 6 is small. On the other hand, in the first yttrium oxyfluoride sintered body 2 (first region), the YF3 structure 6 is small and large, so the Y5O4F7 structure 5 and the YF3 structure 6 are larger than those in the interface region 1. In addition, the structure of the second yttrium oxyfluoride sintered body (second region) is equivalent in size to that of the first region, so that the structure of the interface region is finer than that of the second region.
[0069] Using Figures 3 to 5, the porosity of the first yttrium oxyfluoride sintered body (first region), the second yttrium oxyfluoride sintered body (second region), and the interface region, the ratio of the Y5O4F7 content to the total content of Y5O4F7 and YF3, and the ratio of the YF3 content, and the thickness of the interface region were measured. In addition, the ratio of the YF3 content in the interface region to the ratio of the YF3 content in the first yttrium oxyfluoride sintered body (first region) and the second yttrium oxyfluoride sintered body (second region) was calculated. These are shown in Table 1. The porosity of the second yttrium oxyfluoride sintered body (second region), the ratio of the content of Y5O4F7 to the total content of Y5O4F7 and YF3, and the ratio of the content of YF3 are the same as those of the first yttrium oxyfluoride sintered body (first region) because they are originally made of the same material and have undergone the same process, and are therefore omitted in Table 1.
[0070] Example 2 Similarly to Example 1, one yttrium oxyfluoride sintered body (approximately φ20 mm) was prepared and cut into a semicircular shape to obtain a first yttrium oxyfluoride sintered body and a second yttrium oxyfluoride sintered body. The same Y5O4F7 powder and YF3 powder as in Example 1 were mixed in ethanol in the same ratio as in Example 1 to obtain a slurry. The obtained slurry was applied to the center of the first yttrium oxyfluoride sintered body, pressed to push out excess slurry from the edge of the joining surface, and then dried at 50°C for 3 hours and sintered at 1000°C in an argon atmosphere. The obtained first yttrium oxyfluoride sintered body and the second yttrium oxyfluoride sintered body were bonded to each other without deformation, and became a single plate (bonded body of yttrium oxyfluoride sintered bodies).
[0071] FIG. 6 is a scanning electron microscope photograph of a cross section of the joined body of yttrium oxyfluoride sintered bodies obtained in Example 2. In the bonded body 10 of yttrium oxyfluoride sintered bodies shown in Fig. 6, the dark layered part in the center where island-shaped particles are scattered is the interface region 1, the light-colored part above the interface region is the first yttrium oxyfluoride sintered body 2 (first region), and the light-colored part below the interface region is the second yttrium oxyfluoride sintered body 3 (second region). The dark-colored part is the resin filled with resin, and pores 4 exist in this part. As shown in FIG. 6, the interface region 1 between the first yttrium oxyfluoride sintered body 2 (first region) and the second yttrium oxyfluoride sintered body 3 (second region) had a clear boundary even after sintering. In Example 2, since the powders of Y5O4F7 and YF3 used in the slurry both aggregated, it is believed that the interface region after sintering became clearly identifiable.
[0072] Using FIG. 6, the porosity of the first yttrium oxyfluoride sintered body (first region), the second yttrium oxyfluoride sintered body (second region), and the interface region, the ratio of the Y5O4F7 content to the total content of Y5O4F7 and YF3, and the ratio of the YF3 content to the total content of Y5O4F7 and YF3, and the thickness of the interface region were measured. In addition, the ratio of the YF3 content in the interface region to the YF3 content in the first yttrium oxyfluoride sintered body (first region) was calculated. These are shown in Table 1.
[0073] Example 3 Similarly to Example 1, one yttrium oxyfluoride sintered body (approximately φ20 mm) was prepared and cut into a semicircular shape to obtain a first yttrium oxyfluoride sintered body and a second yttrium oxyfluoride sintered body. The Y5O4F7 and YF3 powders were first crushed into agglomerated particles in a mortar until they became individual particles. 70 parts by weight of Y5O4F7 powder having an average particle size of 3 μm and 30 parts by weight of YF3 powder having an average particle size of 3 μm were mixed in 50 parts by weight of ethanol to obtain a slurry. The obtained slurry was applied to the center of the first yttrium oxyfluoride sintered body, pressed to push out excess slurry from the edge of the joining surface, and then dried at 50°C for 3 hours and sintered at 1000°C in an argon atmosphere. The obtained first yttrium oxyfluoride sintered body and the second yttrium oxyfluoride sintered body were bonded to each other without being deformed, and became one plate (bonded body of yttrium oxyfluoride sintered bodies).
[0074] FIG. 7 is a scanning electron microscope photograph of a cross section of the joined body of yttrium oxyfluoride sintered bodies obtained in Example 3. In the yttrium oxyfluoride sintered body joint 10 shown in FIG. 7, the interface region 1 having many pores 4 sandwiched between the first yttrium oxyfluoride sintered body 2 (first region) and the second yttrium oxyfluoride sintered body 3 (second region) is thinner than in Example 2, and the boundary is unclear, and the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the interface region was determined as the ratio at the center line. In Example 3, it is believed that the Y5O4F7 and YF3 powders used in the slurry did not aggregate, making it possible to thin the interface region after sintering.
[0075] Using FIG. 7, the porosity of the first yttrium oxyfluoride sintered body (first region), the second yttrium oxyfluoride sintered body (second region), and the interface region, the ratio of the Y5O4F7 content to the total content of Y5O4F7 and YF3, and the ratio of the YF3 content to the total content of Y5O4F7 and YF3, and the thickness of the interface region were measured. In addition, the ratio of the YF3 content in the interface region to the YF3 content in the first yttrium oxyfluoride sintered body (first region) was calculated. These are shown in Table 1.
[0076] [Table 1]
[0077] As shown in Table 1, in the joined bodies of yttrium oxyfluoride sintered bodies according to Examples 1 to 3, the porosity of the interface region was within the range of 2 to 60%. In addition, in the joined bodies of the yttrium oxyfluoride sintered bodies according to Examples 1 to 3, the YF3 content in the interface region was higher than the YF3 contents in the first and second regions. Furthermore, in the joined yttrium oxyfluoride sintered bodies according to Examples 1 to 3, the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the interface region was within the range of 101 to 150% of the ratio of the YF3 content to the total content of Y5O4F7 and YF3 in the first and second regions. Therefore, it is presumed that the joined bodies of the yttrium oxyfluoride sintered bodies according to Examples 1 to 3 have a sufficiently small density in the interface region, can suitably disperse thermal stress, and have sufficient joining strength. [Explanation of symbols]
[0078] 1 Interface area 2. First yttrium oxyfluoride sintered body 3. Second yttrium oxyfluoride sintered body 4. Stoma 5. Y5O4F7 Organization 6. Organization of YF3 10. Yttrium oxyfluoride sintered body
Claims
1. A joint of yttrium oxyfluoride sintered bodies comprising a first region and a second region opposed to the first region across an interface region, The interface region has a higher porosity than the first region and the second region. A bonded body of yttrium oxyfluoride sintered bodies, comprising:
2. The bonded body of yttrium oxyfluoride sintered bodies according to claim 1, wherein the interface region has a porosity of 2 to 60%.
3. The conjugate is YF 3 and Y 5 O 4 F 7 and the interface region is made of YF 3 The joined body of yttrium oxyfluoride sintered bodies according to claim 1 or 2, having a high content of yttrium oxyfluoride.
4. The Y of the interface region 5 O 4 F 7 and Y.F. 3 YF relative to the total content 3 The ratio of the contents of Y in the first region and Y in the second region is 5 O 4 F 7 and Y.F. 3 YF relative to the total content 3 The joined body of yttrium oxyfluoride sintered bodies according to claim 3, wherein the ratio of the content of said yttrium oxyfluoride sintered bodies is 101 to 150%.
5. The joined body of yttrium oxyfluoride sintered bodies according to any one of claims 1 to 4, wherein the structure of the interface region is finer than the structures of the first region and the second region.
6. A method for producing the yttrium oxyfluoride sintered body according to any one of claims 1 to 5, A method for producing a joint of yttrium oxyfluoride sintered bodies, comprising a joining step of sandwiching a joining surface of a first yttrium oxyfluoride sintered body and a joining surface of a second yttrium oxyfluoride sintered body between which is sintered a powder of yttrium oxyfluoride having a higher fluorine content than the first and second yttrium oxyfluoride sintered bodies.
7. The method for producing a joined body of yttrium oxyfluoride sintered bodies according to claim 6, wherein the joining step is carried out at 700 to 1200 ° C.
8. The method for producing a joined body of yttrium oxyfluoride sintered bodies according to claim 6 or 7, wherein in the joining step, a slurry containing the yttrium oxyfluoride powder and a solvent is applied.
9. The method for producing a joined body of yttrium oxyfluoride sintered bodies according to claim 8, wherein the solvent is ethanol or methanol.
Citation Information
Patent Citations
Ceramic bonded body and its manufacturing method
JP2003128473A
Ceramic bonded body and method of manufacturing the same
JP2008174443A
Ceramic connector and its manufacturing method
JP2008184352A
Ceramic bonded body and its manufacturing method
JP2010018448A
Corrosion-resistant member and method for producing the same
JP2011136877A